Effects of High-School Size on Student Outcomes:Response to Howley and Howley - Valerie E. Lee (Arizona State University, 2004)
I take issue with several points in the Howleys' reanalysis (Vol. 12 No. 52 of this journal) of "High School Size: Which Works Best and for Whom?" (Lee & Smith, 1997). That the original sample of NELS schools might have underrepresented small rural public schools would not bias results, as they claim. Their assertion that our conclusions about an ideal high-school size privileged excellence over equity ignores the fact that our multilevel analyses explored the two outcomes simultaneously. Neither do I agree that our claim about "ideal size" (600-900) was too narrow, as our paper was clear that our focus was on achievement and its equitable distribution. Perhaps the most important area of disagreement concerns non-linear relationships between school size and achievement gains. Ignoring the skewed distribution of school size, without either transforming or categorizing the variable produces findings that spuriously favor the smallest schools. Our recent involvement as expert witnesses on opposite sides in a court case may have motivated the Howleys' attempt to discredit our work. Finally, I argue that research attempting to establish a direct link between school size and student outcomes may be misguided. Rather, school size influences student outcomes only indirectly, through the academic and social organization of schools. Considerable evidence links these organizational factors to student outcomes (especially learning and its equitable distribution).